EXPRESSING THE COTTON LEXEME IN LINGUISTICS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2023)
This article shows, first of all, the role of cotton in our daily life, its necessity in various sectors of the national economy, and how important it is for the Uzbek nation. Also, attention is paid to the etymology of the words "pahta" in the Uzbek language and "cotton" in the English language. In this work, the use of the lexeme cotton in English and Uzbek languages in different meanings is revealed, they are compared in the two languages, attention is paid to their similarities and differences. The meanings of expressions related to the word cotton are explained with the help of concrete examples.